2021
DOI: 10.1002/hep.32000
|View full text |Cite
|
Sign up to set email alerts
|

YAP/TAZ Suppress Drug Penetration Into Hepatocellular Carcinoma Through Stromal Activation

Abstract: BaCKgRoUND aND aIMS: HCC is the most predominant type of liver cancer affecting 800,000 people globally each year. Various small-molecule compounds targeting diverse oncogenic signaling pathways have been tested for patients with HCC, and clinical outcomes were not satisfactory. In this study, we investigated molecular signaling that determines the efficiency of drug delivery into HCC.appRoaCH aND ReSUltS: Hydrodynamics-based transfection (HT) was performed to develop mouse models for HCC induced by various on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
0
16
0
4
Order By: Relevance
“…[ 26 ] Furthermore, activation of YAP/TAZ signaling was obligated to orchestrate tumor surrounding stromal cells. [ 27 ] These data suggest a possible role of YAP in governing obese‐associated TME. Thus, it is worth investigating the role of YAP/TAZ‐mediated metabolic remodeling in the crosstalk between breast tumors and the TME.…”
Section: Discussionmentioning
confidence: 92%
“…[ 26 ] Furthermore, activation of YAP/TAZ signaling was obligated to orchestrate tumor surrounding stromal cells. [ 27 ] These data suggest a possible role of YAP in governing obese‐associated TME. Thus, it is worth investigating the role of YAP/TAZ‐mediated metabolic remodeling in the crosstalk between breast tumors and the TME.…”
Section: Discussionmentioning
confidence: 92%
“…Cho et al showed how specific oncogenic pathways, such as the yesassociated protein/transcriptional co-activator with PDZ-binding motif (YAP/TAZ) model, can lead to a constitutive 1274 activation of the stromal component impairing the penetration of treatments into the cancer tissue. 88 In fact, besides molecular dissection of mechanisms, animal models are pivotal for therapeutic approaches. Experimental tools include not only models mimicking different risk factors and molecular subgroups but also a wide range of tumor induction techniques, since the liver is highly receptive for any kind of molecules, including nucleic acids and viral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Both the tumor-suppressing or killing effects of drugs themselves and the efficient delivery of drugs into tumors are important for cancer treatment. Based on multicellular HCC organoids containing both HCC cells and diverse stromal cells (ECs, fibroblasts, and hepatic stellate cells) [181], high activity of Yes-associated protein/transcriptional coactivator with PDZ-binding motif signaling was shown to be associated with stromal activation in HCC and suppressed the penetration of verteporfin into tumoroids, indicating that treatments targeting activated cancer stroma might facilitate drug delivery into HCC [181].…”
Section: Discovery Of Novel Anticancer Targets and Promising Drug Can...mentioning
confidence: 99%